1996
DOI: 10.1074/jbc.271.8.4038
|View full text |Cite
|
Sign up to set email alerts
|

Human Enteric Defensins

Abstract: Paneth cells, secretory epithelial cells of the small intestinal crypts, are proposed to contribute to local host defense. Both mouse and human Paneth cells express a collection of antimicrobial proteins, including members of a family of antimicrobial peptides named defensins. In this study, data from an anchored polymerase chain reaction (PCR) strategy suggest that only two defensin mRNA isoforms are expressed in the human small intestine, far fewer than the number expressed in the mouse. The two isoforms det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
89
0
1

Year Published

1996
1996
2018
2018

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 263 publications
(92 citation statements)
references
References 51 publications
2
89
0
1
Order By: Relevance
“…Paneth cells are differentiated cells that exist in the crypt. However, CDX2 protein has been reported to be weakly expressed in adult mouse Paneth cells (41), and a negligible Paneth cell compartment is present in the mid-gestational human fetal jejunum (42). Determination of the net fluorescence intensity for 26 crypts from 8 fetal human jejuna confirmed that cells located in the lowest portion of the crypt expressed significantly (p Ͻ 0.05) lower levels of CDX2 that those located in the upper region of the crypt.…”
Section: Distribution Of Cdx2 In Human and Mouse Intestinal Epitheliumentioning
confidence: 55%
“…Paneth cells are differentiated cells that exist in the crypt. However, CDX2 protein has been reported to be weakly expressed in adult mouse Paneth cells (41), and a negligible Paneth cell compartment is present in the mid-gestational human fetal jejunum (42). Determination of the net fluorescence intensity for 26 crypts from 8 fetal human jejuna confirmed that cells located in the lowest portion of the crypt expressed significantly (p Ͻ 0.05) lower levels of CDX2 that those located in the upper region of the crypt.…”
Section: Distribution Of Cdx2 In Human and Mouse Intestinal Epitheliumentioning
confidence: 55%
“…15 High culture positivity rate was seen in our study as preterm VLBW neonates are more susceptible to infection due to various reasons like lower levels of IgG which are passively transferred during the third trimester; mucous membrane defenses such as secretory immunoglobulin A (IgA), mucin, and defensins have been shown in some studies to be deficient in VLBW neonates and the first line of defense against infection is an intact epidermis and mucous membranes, which are compromised in VLBW infants. 4,[16][17][18] The most common risk factor associated with BACTEC blood culture positivity was prolonged rupture of membranes (PROM) with a positivity rate of 67% followed by urinary tract in infection in mother (58%). In the study done by Maharaja P et al low birth weight followed by PROM were the most common risk factors correlating to sepsis.…”
Section: Discussionmentioning
confidence: 99%
“…Oligonucleotides were radioactively labeled as described (13). PCR products were isolated and subcloned as described (14 (1 ,uM; Collaborative Research), and gentamycin (50 ,ug/ml). The complete medium was tested by the Limulus amebocyte lysate/gel clot assay to be free of bacterial endotoxin.…”
Section: Methodsmentioning
confidence: 99%